2022
DOI: 10.1200/cci.21.00121
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Score: A Simple Model to Predict Immunochemotherapy Tolerability in Patients With Diffuse Large B-Cell Lymphoma

Abstract: PURPOSE Rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP) represents the standard of care for first-line treatment of diffuse large B-cell lymphoma (DLBCL). However, many patients are unable to tolerate R-CHOP and have inferior outcomes. This study aimed to develop a practical tool to help physicians identify patients with newly diagnosed DLBCL unlikely to tolerate a full course of R-CHOP. METHODS We developed a predictive model (Tolerability of R-CHOP in Aggressive Lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…We evaluated the GameRank algorithm on the real-world dataset used in Harris et al (2022) We compared the time, performance as measured by area under the ROC curve and bias between hold-out and validation sets for GameRank, random, forward, backward and the bidirectional selection algorithms for feature selection ( Table 1 ). We observed that GameRank, while being slower than random search and forward selection for very small variable sizes, maintains a very stable runtime independent of the number of features selected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the GameRank algorithm on the real-world dataset used in Harris et al (2022) We compared the time, performance as measured by area under the ROC curve and bias between hold-out and validation sets for GameRank, random, forward, backward and the bidirectional selection algorithms for feature selection ( Table 1 ). We observed that GameRank, while being slower than random search and forward selection for very small variable sizes, maintains a very stable runtime independent of the number of features selected.…”
Section: Resultsmentioning
confidence: 99%
“…Before variable selection makes sense, a thorough review of each included variable is essential. From our experience, Harris et al (2022) , clinical variables can be degenerate, show high distribution skew or may even be multi-modal. Therefore, we provide methods to evaluate variable transformation (sqrt, cube root, log), e.g.…”
Section: R Package and Its Usagementioning
confidence: 98%
See 1 more Smart Citation
“…Contudo, existem muitas semelhanças entre as variáveis utilizadas e este processo de elaboração de indicadores específicos para avaliação de toxicidade neste grupo é importante, pois conseguem ser superiores aos atuais preditores de prognóstico e funcionalidade ao menos ao predizer a toxicidade da quimioterapia. (HARRIS et al, 2022) O tratamento das leucemias e linfomas de uma forma geral utilizam tratamento de primeira linha com protocolos de quimioterapia com potencial de toxicidade elevado, sendo esse tipo de tratamento evitado em grupos de pessoas idosas, que acabam realizando esquemas alternativos e de menor intensidade, mas com menor potencial de cura. Isso ocorre por uma avaliação de risco de toxicidade que muitas vezes é intuitiva levando em consideração apenas a idade.…”
Section: Discussionunclassified
“…Desse modo, a elaboração de indicadores específicos para avaliação de toxicidade têm mostrado resultados superiores aos atuais preditores de prognóstico e funcionalidade, ao menos em predizer a toxicidade da quimioterapia (HARRIS et al, 2022) .…”
Section: Introductionunclassified